Clinical pharmacist as a healthcare team member in patient management: Need or necessary evil? - Štuhec, Matej (Anali PAZU, 2022)
The clinical pharmacist inclusion in the patient treatment process including ward roundings and department work is one of the best approaches in medical errors reducing. There are supportive data obtained from the highest quality of well-designed clinical trials and meta-analyzes (Ia evidence) for this type of service. Although the positive effects of this collaboration have been described frequently, a cooperation in real clinical practice often does not follow these positive evidences. In this paper, the recommendations, good and bad practices including current Slovenian situation within this field has been summarized. This contribution can serve as a help to physicians and clinical pharmacists and, in particular, hospital leaders, to establish appropriate forms of collaboration leading to optimal clinical and economic outcomes.
Keywords: clinical pharmacy; healthcare team membership; evidences; Slovenian systems; optimization